2020
DOI: 10.1021/acs.iecr.0c03717
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Influence in Real-Time Monitoring of Fed-Batch Ethanol Fermentation by Mid-Infrared Spectroscopy

Abstract: Fourier transform mid-infrared (FT-MIR) spectroscopy is a fast, accurate, and practical technique for the quantitative analysis of compounds during ethanol fermentation. However, it is very temperature sensitive. This study aimed to develop a methodology for the real-time monitoring of fed-batch ethanol fermentations, taking into account the thermal fluctuations in the industrial process (in the range 30−35 °C). The use of FT-MIR combined with partial least squares (PLS) regression was evaluated as a tool to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The calibration models showed low RMSECV values for water (0.00114) and ethanol (0.000118). As reported in the literature, 33,34 these low RMSECV values indicated that the models presented satisfactory performance.…”
supporting
confidence: 79%
“…The calibration models showed low RMSECV values for water (0.00114) and ethanol (0.000118). As reported in the literature, 33,34 these low RMSECV values indicated that the models presented satisfactory performance.…”
supporting
confidence: 79%
“…The FT-MIR technique is an advanced and accurate tool for the determination of metabolites during ethanol fermentation. , The present approach using the gas phase to quantify ethanol overcomes the challenges related to the mode of operation and the temperature of the samples since a calibration curve is not required for each mode and the quantitation in the gas phase is independent of the reactor operating temperature. In addition, the present technique does not require sample treatment, minimizes the experimental effort in laboratory analyses, and is effective for real-time fermentation monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of liquid phase ethanol using infrared spectroscopy has been widely applied in fermentative processes such as those used for first-generation and second-generation ethanol production, , acetone-butanol-ethanol (ABE) fermentation, and production of fermented beverages. , This method offers important advantages, compared to other techniques, since it is nondestructive and minimally invasive and enables the rapid identification and quantification of specific analytes in complex media . However, difficulties inherent to liquid phase sampling must be overcome, such as the lack of homogeneity of the samples (which are therefore not fully representative of the process), as well as the formation of gas bubbles and biofilms on the detection surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart rate change curve is mainly for analyzing the data of the athlete's heart rate change during training with an intuitive curve rise and fall graph, the heart rate distribution graph shows the percentage of the athlete's heart rate in this training during the test time, the heart rate list can clearly see the specific heart rate value of the athlete every 5 seconds in the test phase through the data column, the heart rate segment summary shows the percentage of the athlete's heart rate under the target heart rate, within the target heart rate range, and higher than the target heart rate during the training period. 6…”
Section: Selection Of Experimental Equipmentmentioning
confidence: 99%